Teaching Tajweed using game-based learning / Aisar Nazirah Alias - Alias, Aisar Nazirah (2016)
“Teaching tajwid using Game-Based Learning” is a game-based learning application that is built for primary school students to enrich their knowledge on tajweed rules. The most method of teaching which through face-to-face is cannot be carried out, since the class hinders the interaction required between students and teachers due to the limitation of time. The objective of this application is to design a game to teach tajweed rules for children using the principle of Game-based learning. Second objective is to develop the game and last objective is to test the usability of the game. Multimedia elements have been added in this application such as text and animation. Gamification input also included in this application, for instant actions and rewards. Usability test has been conducted to the respondents in Sekolah Rendah Agama (JAIM) Felcra Sri Mendapat which participated in the pre and post testing of the application. The result has shown that the students’ knowledge has increased after using the application. Overall, there is still enhancement that could be proposed for this project in the future such as building the application for another tajweed rules and added narrators’ voice.